2009
DOI: 10.1007/s11224-009-9560-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on lithocholyl-N-(2-aminoethyl)amide in the solid state

Abstract: The synthetic procedure of lithocholyl-N-(2-aminoethyl)amide yielded a mixture of several forms detected by solid state 13 C CP/MAS NMR although the solution state NMR unambiguously ascertained that the compound was pure. By recrystallization from various solvents one pure polymorph alongside with four solvates were isolated. The structures of the pure polymorph and the solvates were characterized by 13 C and 15 N CP/MAS NMR and powder X-ray diffraction (PXRD) methods. Variable contact time and dipolar dephasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…5d) indicate the presence of a wider array of structural elements in our gels. In addition, the variability in bands observed in the IR spectra indicated that the polymorphism in the studied systems can be diverse, as reported previously for 1 [85]. Systems, where the gel was formed by vesicles or spherical colloidal aggregates rather than the more common fibrous structures have occasionally been described in the literature [40,78,79,[86][87][88][89].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…5d) indicate the presence of a wider array of structural elements in our gels. In addition, the variability in bands observed in the IR spectra indicated that the polymorphism in the studied systems can be diverse, as reported previously for 1 [85]. Systems, where the gel was formed by vesicles or spherical colloidal aggregates rather than the more common fibrous structures have occasionally been described in the literature [40,78,79,[86][87][88][89].…”
Section: Discussionsupporting
confidence: 69%
“…For a series of low molecular weight gelators based on bile acid esters, Nonappa et al [36] concluded that the xerogels obtained were solvates in none of the cases. On the contrary, Ahonen et al exemplified in their studies on polymorphism of 1 [85] that the xerogel of the compound from chlorobenzene was a solvate. Solvate-formation would explain the strong signal of chlorobenzene, which was present even after extensive drying in vacuum, observed in the IR spectrum of the chlorobenzene xerogel of 1 (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The gelators N-(2-aminoethyl)-3α-hydroxy-5β-cholan-24-amide [32][33][34][35][36][37] 1 and N-(4-aminobutyl)-3α-hydroxy-5β-cholan-24-amide [32] 2 were synthesized, purified, and characterized as described previously. The used solvents included chlorobenzene (Acros Organics, 99+%), bromobenzene (Acros Organics, 99%), iodobenzene (Fluka, > 99% puriss.…”
Section: Methodsmentioning
confidence: 99%
“…2. The signals were assigned as listed in Table 2, based on previous studies (Lüdemann and Nimz 1973;Krohn et al 1989;Ahonen et al 2010;He et al 2012). According to the comparison of the spectra of UL and OL, the intensity of signals No.…”
Section: Cp/mas 13 C-nmr Analysismentioning
confidence: 99%